KAJIAN PENGELOLAAN DANA DESA SEBAGAI PERWUJUDAN TATA KELOLA KEUANGAN DESA - Niken Kusumawardani (TECHNOBIZ : International Journal of Business, 2020)
This study aims to find out empirically the management of village funds carried out by village officials in order to realize the financial management of village funds mandated by the Village Law. Village fund management in this study focuses on the availability of BUMDes priority programs. The hypothesis in this study is transparency (X1), accountability (X2), community participation (X3), effectiveness (X4) and BUMDes (X5) influencing the management of village funds (Y). This study uses primary data through a questionnaire, with a total of 90 respondents. The sample of the research is the village officials and BUMDes officials in Punggur District, Central Lampung Regency. Hypothesis testing using software PLS, through multiple regression analysis test equipment. The results showed that the variables of transparency, accountability, community participation, effectiveness, and BUMDes had a positive effect on village fund management in Punggur District, Central Lampung Regency.